Research on Collaborative Innovation Strategy of Smart Supply Chain in the Big Data Era - He Wang; Xiang Huang (E3S Web of Conferences, 2021)
With the continuous emergence of new technologies such as Artificial intelligence, big data, Cloud computing and IOT, technology accelerates integration and innovation, and data dividends have continued to emerge. At the same time, China’s “Internet Action Plan”, “Made in China 2025”, “Digital China” and other national strategies have been implemented in depth, China’s social and economic development has entered the era of big data. As the basic industry of the national economy. The logistics industry will also accelerate changes, and it has become a development trend for companies to use new technologies to realize smart supply chain collaborative innovation. The paper analyzes the development opportunities of smart supply chain in the Big Data Era, summarizes the problems encountered in the application of big data in the smart supply chain at this stage, and finally puts forward the collaborative innovation strategy for smart supply chain in the Big Data Era, Providing reference for collaborative innovation development of enterprise supply chain.